PENINGKATAN KETERAMPILAN BERBICARA TEKS PROSEDUR DENGAN METODE DEMONSTRASI MELALUI MEDIA BENDA REALIA PADA SISWA SMP - Umiyatun Umiyatun (Jurnal Pendidikan Surya Edukasi (JPSE), 2018)
The ninth students of IX A of SMP N 2 Purworejo have some problems in speaking skill. They often do mistakes not only grammar but also pronunciation. They have limited vocabulary  so they can’t speak English fluently. Moreover. They are afraid of speaking English because they don’t have strong confidence. Based on those problems, I try to make teaching learning process innovative and effective especially for speaking skill in procedure by using the demonstration method. The objective of my research is to find out whether   the students’ speaking skill in  procedure can be improved through the  demonstration method or not. In this research, I collected the data by using qualitative and quantitative methods. The qualitative data was taken by using observation, recorded data and interview. While,  the quantitative data was taken by using test. In cycle 1, there were 22 students (68,75%) who fulfilled the passing grade while the rest, 10 students (31,25%) still did not pass the passing grade. Then, in cycle 2, there were 87,50% or 28 students who fulfilled the passing grade while the rest, 12,50 % or 4 student still did not pass the passing grade Therefore, it could be concluded that the ninth students of IX A in the first  semester of ‘SMP N ‘2 Purworejo in the academic year 2017/2018 can improve their speaking skill in procedure text through the  demonstration method. Based on the observation and the interview, they are interested with this method through  real things.  They have strong confidence and high motivation to speak English. I believe that the demonstration method can improve the students’speaking skill in not only procedure text but also  any other texts. Keywords: Speaking Skill, Procedure , demonstration